Transforming Narratives: The Influence OF Digital Storytelling on Traditional Narratives in English Literature - Zhang, Yuhong (Pacific International Journal, 2024)
This study investigates the influence of digital storytelling on traditional narrative forms in English literature. Specifically, it examines how digital storytelling transformation (IDST) impacts participants' understanding of traditional narratives (UTN) and their awareness of digital platforms in storytelling (ADP). Additionally, the research explores the relationship and differences between digital storytelling and traditional narratives (RDTN), as well as the influence of digital technology and media on narrative methods (IDTM). Through this exploration, the study aims to provide insights into the evolving landscape of narrative and the implications for literary education. A mixed-methods approach was employed, utilizing a questionnaire distributed to participants from three universities in Zhejiang Province. The questionnaire assessed their understanding of traditional narratives, awareness of digital platforms, perceptions of the relationship between digital storytelling and traditional narratives, and the impact of digital technology on traditional narrative in English literature. The analysis revealed high reliability scores for the understanding of traditional narratives (UTN) and awareness of digital platforms (ADP), indicating a solid foundation for engaging with digital storytelling. Participants demonstrated a nuanced understanding of the relationship and differences between digital and traditional narratives (RDTN), with scores reflecting an appreciation for how digital storytelling complements traditional forms. However, the slightly lower score for the influence of digital technology on narrative methods (IDTM) suggests a need for further exploration of how digital tools can transform narrative practices.